Analysis Of Taxpayer Satisfaction Affected By Service Quality - Rohmawati Rohmawati; Yanto Yanto (Accounting Study Program, Faculty of Economics and Business, 2022)
This research is a quantitative research that aims to test empirically the reliability, responsiveness, assurance, empathy, physical form and online services on taxpayer satisfaction. The data used is primary data. Data collection was carried out by distributing questionnaires to taxpayers at KPP Pratama Jepara. The number of taxpayer respondents used as a sample is 100 people. So that the total questionnaires distributed were 100 questionnaires. Data processing is done using SPSS version 20.0 for Windows. The results of the study show that reliability, responsiveness, assurance, empathy, and physical appearance do not affect taxpayer satisfaction, while online services have an effect on taxpayer satisfaction.